HUBUNGAN DUKUNGAN KELUARGA DALAM PENGENDALIAN HIPERTENSI DENGAN PEMENUHAN GIZI PASIEN LANSIA (LITERATURE REVIEW) - Ni Made Dwi Endriani; I Putu Suiraoka; Ni Komang Wiardani (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2023)
The prevalence of hypertension has increased significantly in patients aged 60 years and over. The emergence of hypertension is related to lifestyle factors and diet. Efforts are made to reduce the risk of increasing blood pressure in the elderly, one of which is with family support and nutritional fulfillment. The family becomes a support system in the life of people with hypertension, so that the situation they experience does not get worse and avoid complications due to hypertension. The purpose of this study was to describe the relationship between family support in controlling hypertension with the fulfillment of nutrition and blood pressure in the elderly. This research is a literature review in May 2021 with qualitative research methods. The research data includes data on respondent characteristics (gender, age), family support, nutritional fulfillment for the elderly, and hypertension in the elderly, then the journals are tabulated and analyzed qualitatively. The results of the literature review of family support are mostly in the good category. Fulfillment of nutrition is included in the fulfilled category. Based on the literature review, it is known that most of the samples have hypertension in stage I and pre-hypertension. Based on the analysis, 10 journals stated that there was a significant relationship between family support in controlling hypertension and the fulfillment of nutrition and blood pressure in the elderly (p 0.05).Keyword : Family Support, Nutritional Fulfillment, Hypertensional Control, Elderly